TAX COMPLIANCE AS AN INSTRUMENT FOR STRENGTHENING THE FISCAL POTENTIAL OF STATE AND LOCAL BUDGETS (INNOVATIVE ECONOMY, 2024)
Krupka M.I., Tkachyk F.P.  TAX COMPLIANCE AS AN INSTRUMENT FOR STRENGTHENING THE FISCAL POTENTIAL OF STATE AND LOCAL BUDGETSPurpose. The aim of the article is to study current trends in the formation and implementation of compliance in the Ukrainian practice of tax risk management in order to increase the fiscal potential of state and local budgets.Methodology of research. The following general scientific and special methods of scientific research were used in the article to solve the set goal: system analysis – for a comprehensive study of the essence of tax compliance and its institutional and legal aspects, which made it possible to determine the main ways of minimizing tax risks; functional analysis – when investigating the fiscal and motivating role of tax compliance; structural – when assessing the structure of tax risks and their impact on the execution of state and local budgets in Ukraine; the method of comparison – in the study of foreign experience of tax risk management based on compliance; generalization and observation – during the analysis of causes and factors affecting the effectiveness of taxation and ensuring the sustainable development of the state; induction, deduction and other methods of scientific knowledge.Findings. The essential determinants of the use of compliance in tax risk management processes are highlighted. The fiscal and motivational role of tax compliance in the accumulation of state and local budget revenues is substantiated. The indicators of the activity of fiscal institutions in the process of implementing tax compliance into the Ukrainian practice of minimizing fraudulent and corrupt phenomena in taxation are analysed.The practical role of the functioning of the unit responsible for the implementation of tax compliance in tax authorities, taking into account foreign experience and within the framework of the implementation of the National Revenue Strategy, has been proven, which will improve the procedures for working out tax risks and forming partnership relations with taxpayers. This aspect will contribute to the conscientious fulfilment of tax obligations, which will positively affect the accumulation of financial resources of the state and local budgets in Ukraine in the conditions of combating wartime risks.Originality. The theoretical and methodological approaches to the implementation of dominant compliance in the system of combating tax risks and fiscal losses based on the results of the administration of tax payments to budgets of all levels have gained further development.Practical value. The obtained results can be useful for legislators, specialists in the field of taxation, scientific and pedagogical workers and other interested persons, contributing to the development of effective strategies for overcoming tax risks in order to strengthen the fiscal potential of the state and territorial communities.Key words: fiscal policy, budgetary resources, compliance, tax risk management, tax administration, fiscal partnership.
Keywords: fiscal policy; budgetary resources; compliance; tax risk management; tax administration; fiscal partnership.